1982
DOI: 10.1111/j.2042-3306.1982.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic fractures of the equine hock: A report of 13 cases

Abstract: Summary The clinical features, radiographic findings, management and outcome in 13 cases of traumatic fracture of the hock joint are reported. The principal fracture sites were the distal tibial malleoli (5 cases), the fibular tarsal bone (4 cases), the tibial tarsal bone (3 cases) and the proximal end of metatarsal IV (one case). An additional small chip fracture of the central tarsal was noted in 2 cases. Three horses were destroyed immediately after diagnosis, 2 failed to recover following surgical interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 3 publications
1
57
3
Order By: Relevance
“…Results of this study were better than those reported in previous studies 2, 10 and in contrast to those of reports [3][4][5][6][7][8][9] in which horses with osteomyelitis of the ST were considered to have a good to fair chance of surviving but only a fair to poor chance of returning to their previous use. Six of the 10 horses in this study returned to their previous use, and 1 additional horse was sound but was retired for unrelated reasons.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Results of this study were better than those reported in previous studies 2, 10 and in contrast to those of reports [3][4][5][6][7][8][9] in which horses with osteomyelitis of the ST were considered to have a good to fair chance of surviving but only a fair to poor chance of returning to their previous use. Six of the 10 horses in this study returned to their previous use, and 1 additional horse was sound but was retired for unrelated reasons.…”
Section: Discussioncontrasting
confidence: 95%
“…

T he sustentaculum tali (ST) is the enlargement of the distal aspect of the medial surface of the calcaneus and forms a groove for passage of the tendon of the lateral digital flexor (LDF) muscle. [3][4][5][6][7][8][9] Typical clinical abnormalities in affected horses include swelling of the soft tissues of the tarsus, severe lameness, distension of the tarsal sheath, and effusion of the tarsocrural joint. 2 The LDF tendon is enveloped by the tarsal sheath, which extends 12 to 16 cm proximal and 4 to 6 cm distal to the tarsocrural joint, ending in the proximal third of the metatarsus.

…”
mentioning
confidence: 99%
“…Tarsal collateral injuries have been identified solely affecting the ligament and have also been reported in combination with enthesophytes at the origin or insertion (Jakovljevic et al . 1982; Phillips 1986; Boero et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the lateral or medial malleoli of the distal aspect of the tibia occur infrequently but are the most commonly reported types of fractures involving the tarsocrural (TC) joint (Jakovljevic et al . 1982).…”
Section: Introductionmentioning
confidence: 99%
“…1982). They are acute, traumatic injuries that are usually the result of a fall or a kick; subsequently horses typically manifest severe lameness, marked TC effusion and soft tissue swelling of the affected side (Jakovljevic et al . 1982; Wright 1992; O'Neill and Bladon 2010; Smith and Wright 2011).…”
Section: Introductionmentioning
confidence: 99%